Hematological Parameters of White Blood Cells in Fishing Communities of Smokers and Non-Smokers With Wet Cupping Therapy - Indriono Hadi; Lilin Rosyanti; Akhmad Akhmad; Alfi Syahar Yakub (Health Notions, 2023)
Complementary therapy is a therapeutic therapy to improve people's health status by preventing and treating disease and improving health. The aim of this study is to determine the effect of complementary wet cupping therapy on changes in white blood cells hematological parameters in smoking and non-smoking fishing communities. The research design used a pretest-posttest design. The sample size was 52 fishermen aged 20-50 years, which were divided into two groups, namely (1) group A: 26 smoking fishermen who were given wet cupping therapy, (2) group B: 26 non-smoker fishermen were also given wet cupping therapy. This research took place at the Coastal Health Center of Lalongasomeeto. Data were analyzed using the Paired Samples T-Test and the Wilcoxon test. There was a change after being given wet cupping therapy, the value of hematological parameters related to white blood cells in smoking fishermen, in WBC, neutrophils, and lymphocytes with a p-value less than 0.05, whereas in non-smoking fishermen after wet cupping therapy, p-value less than 0.05 was found in WBCs, neutrophils, basophils, neutrophils, and eosinophils. Complementary wet cupping therapy is beneficial and recommended to improve the health and endurance of coastal communities, fishermen who smoke and fishermen who do not smoke. Keywords: fishermen; smoking; wet cupping therapy; hematology; white blood cell